A Curious Case of Progressive Respiratory Failure Due to Anterior Spinal Cord Infarction in an Adolescent Boy: A Case Report and Review of the Literature - Putzeys, Caroline Chinchilla; Batra, Mansi; Maertens, Paul; Sharma, Kamal (Journal of Pediatric Neurology, 2021)
Clinical features of cervical spontaneous spinal cord infarctions (SSCIs) remain poorly described in the literature. The goal of this article was to improve recognition of cervical SSCI, a rare but life-threatening condition. We presented a 15-year-old adolescent male patient who developed neck pain with weakness and numbness in all four limbs half an hour after returning from a hike in the late afternoon. The next morning, he was brought to the emergency room due to persistent weakness, vomiting, and progressive respiratory distress. He was promptly intubated for airway protection. Pupils were 2 mm, sluggishly reactive, and all four extremities were flaccid. He was found to have anterior spinal cord syndrome. Light touch (brush) was normal down to the posterior aspect of shoulders. Cervical magnetic resonance imaging (MRI) showed increased T2/short-tau inversion recovery and decreased T1 signal of the anterior spinal cord from C3 to C7. Four days later, MRI of the spinal cord showed restricted diffusion of anterior spinal cord consistent with radicular artery territory infarction. The work-ups for infection, thrombosis, and cardioembolism were all negative. Three months later, he still had incomplete Brown-Séquard's syndrome, as position sense was preserved. There was in addition bilateral loss of pain and temperature sensations below the clavicles. MRI showed cervical myelomalacia most severe between C3 and C5. Furthermore, MRI showed changes in C3–C4 intervertebral disc, consistent with a fibrocartilaginous embolism via retrograde arterial route into the anterior spinal artery. This article demonstrates the importance of recognizing subtle clinical clues leading to cervical SSCI diagnosis.
Keywords: pediatric; cord atrophy; Horner's syndrome; vomiting